2004
DOI: 10.1074/jbc.m310423200
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Cloning of an Endogenous Protein Inhibitor of Carp Nephrosin, an Astacin Metalloproteinase

Abstract: Nephrosin is a newly discovered member of the astacin family. It is a secreted proteinase and is present in carp head kidney, kidney, and spleen, all of which are responsible for immune and hematopoietic functions in fish. A complex formed by nephrosin and its inhibitor was purified from carp kidney extract by heparin affinity column chromatography. The presence of the nephrosin-inhibitor complex in different tissues was examined by immunoblotting with polyclonal antisera against the purified nephrosin inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…); several proteins that localize to CyHV‐3‐affected areas were identified including nephrosis precursor, fetuin short form and three other glial‐associated proteins (Kálmán ; Tsai et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…); several proteins that localize to CyHV‐3‐affected areas were identified including nephrosis precursor, fetuin short form and three other glial‐associated proteins (Kálmán ; Tsai et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Three proteins were identified in both analyses, the gel solution contained an additional six proteins, and the unmodified solution contained an additional 12 proteins (Table 3). CyHV-3 is known to affect kidneys, spleen and brain of carp (Ronen et al 2003;Pikarsky et al 2004;Miyazaki et al 2008); several proteins that localize to CyHV-3-affected areas were identified including nephrosis precursor, fetuin short form and three other glial-associated proteins (K alm an 1998; Tsai et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is a secreted proteinase and is present in carp head kidney, posterior kidney, and spleen, all of which are responsible for immune and haematopoietic functions in fish (Tsai et al, 2004). We characterised nephrosin as an up-regulated gene in gill of saltwateracclimated sea bass.…”
Section: The Case Of Nephrosin a Gene Potentially Involved In Regulamentioning
confidence: 98%
“…Interestingly, there is a fi sh astacin from carp head kidney (a hematopoietic organ) which circulates in the blood stream in complex with a specifi c protein inhibitor. Originally, this enzyme was termed ' nephrosin ' (Hung et al , 1997 ) and its inhibitor ' nephrosin inhibitor ' (Tsai et al , 2004 ). The nephrosin inhibitor is a homolog of fetuin, a large plasma protein with many functions.…”
Section: Protein Inhibitorsmentioning
confidence: 99%